АНАЛИЗ ИНВЕСТИЦИОННОГО ПОТЕНЦИАЛА АГРОПРОМЫШЛЕННОГО КОМПЛЕКСА РК - D. N. Akinbekova (Экономика: стратегия и практика)
The purpose of this article is to analyze the investment attractiveness of the agro-industrial complex of the Republic of Kazakhstan and determine the priorities of its investment potential. In this article, methods to obtain, refine and adjust the results from the various stages of the research were applied, in particular: scientific abstraction method, comparative analysis method, and economic-statistical method.The articles are considered the volume, structure and dynamics of investments in fixed capital in the context of the regions of the Republic of Kazakhstan. The interrelation of such indicators as gross regional product (GRP), investment in fixed capital and the volume of investment per capital is analyzed. The priorities of the investment potential of the agro-industrial complex of the Republic of Kazakhstan are identified and justified.